Elementary School Teachers’ Proficiency: Philippine Professional Standards under Flexible Teaching Modality - Maloloy-on, Melisa C; Arnado, Alvic A (International Journal of Membrane Science and Technology, 2023)
The study evaluated the teaching proficiency of elementary school teachers in Nasipit, Agusan del Norte, Philippines, under flexible teaching and learning modality based on the Philippine Professional Standard for Teachers (PPST) using a descriptive-correlational research design and stratified random sampling. The research aimed to investigate the teachers' proficiency in fostering education for sustainable development by applying its principles to teaching and learning activities. The study found a significant relationship between teachers' proficiency level based on the PPST and their teaching performance. Regression analysis revealed that Content Knowledge Pedagogy, Diversity of Learners, and Professional Growth and Professional Development are significant predictors of teaching performance. These findings are consistent with previous studies emphasizing the importance of teachers' subject matter knowledge, pedagogical content knowledge, and multicultural education in promoting student learning and improving the quality of education. Ongoing professional development can enhance teachers' effectiveness in the classroom, as demonstrated by the significant contribution of Professional Growth and Professional Development to teaching performance